Bidirectional extracellular matrix signaling during tissue morphogenesis - Gjorevski, Nikolce (2009)
Normal tissue development and function are regulated by the interplay between cells and their surrounding extracellular matrix (ECM). The ECM provides biochemical and mechanical contextual information that is conveyed from the cell membrane through the cytoskeleton to the nucleus to direct cell phenotype. Cells, in turn, remodel the ECM and thereby sculpt their local microenvironment. Here we review the mechanisms by which cells interact with, respond to, and influence the ECM, with particular emphasis placed on the role of this bidirectional communication during tissue morphogenesis. We also discuss the implications for successful engineering of functional tissues ex vivo.